2016
DOI: 10.1108/jmhtep-01-2016-0008
|View full text |Cite
|
Sign up to set email alerts
|

Aims for service user involvement in mental health training: staying human

Abstract: Purpose The purpose of this paper is to examine the impact of service user involvement in mental health training but little is known about what staff, trainees and service users themselves want to achieve. Design/methodology/approach Three separate focus groups were held with service users, training staff and trainees associated with a clinical psychology training programme. Thematic analysis was used to identify aims for involvement. Findings All groups wanted to ensure that future professionals “remained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 19 publications
(19 reference statements)
2
16
0
Order By: Relevance
“…The humanising effects of SUAC involvement on academics found in this study also resonate with those of Lea et al (2016) and underline the grounding effect of such work as being very important in reminding them of the core value base of their respective professions and the need to be constantly aware of issues of professional power. Findings such as these represent new positive knowledge regarding the SUAC contribution at HE and might be seen as part of a positive trajectory over the past two decades of activity and research in this area.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The humanising effects of SUAC involvement on academics found in this study also resonate with those of Lea et al (2016) and underline the grounding effect of such work as being very important in reminding them of the core value base of their respective professions and the need to be constantly aware of issues of professional power. Findings such as these represent new positive knowledge regarding the SUAC contribution at HE and might be seen as part of a positive trajectory over the past two decades of activity and research in this area.…”
Section: Discussionsupporting
confidence: 75%
“…This study did not find that academics perceived SUACs to be primarily involved for their own personal development (Webber and Robinson, 2012), although the benefits to SUACs from HE involvement were seen as significant, as recognised by Rooney, Unwin and Osborne (2016). More significantly, staff perceived that SUAC involvement added value and knowledge to student experiences, while simultaneously enriching the working lives of academics, particularly in respect of challenges presented to value bases and to traditional models of power and knowledge hierarchies (Lea et al, 2016). Furthermore, staff cited how working alongside SUACs had acted as a form of CPD, particularly when workload pressures (Graham, 2015) preclude staff taking up more formal CPD opportunities.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The valuable contribution that 'experts by experience' can make to applied psychology and psychotherapy training programmes has attracted increasing attention over recent years (e.g. Lea et al, 2016), and researchers could usefully think about ways to involve expert clients in Client experiences and expectations of therapy 21 research and evaluation activities (for example, client-led interviews) to help elicit balanced accounts of the client perspective of psychological therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In the wider literature, service-users and carers have voiced similar motivations for involvement work (Lea et al, 2016;Anghel & Ramon, 2009;Turner et al, 2000) whilst students have reported that service-user involvement in teaching has given them a greater insight into service-users' perspectives, greater empathy (Repper & Breeze, 2007;Rush, 2008) and ideas about how to improve mental health services (Happell et al, 2014).…”
Section: Contributing To Meaningful Changes In Mental Health Carementioning
confidence: 99%